Surveillance of infection associated with external ventricular drains: proposed methodology and results from a pilot study. Issue 2 (February 2017) - Humphreys, H.; Jenks, P.; Wilson, J.; Weston, V.; Bayston, R.; Waterhouse, C.; Moore, A.
Summary: Background: The insertion of external ventricular drains (EVDs) is necessary in some neurosurgical patients, but increases the risk of meningitis/ventriculitis. While there are well-recognized risk factors, the proportion of patients who develop meningitis/ventriculitis varies partly due to differences in definitions. A multi-disciplinary working group was established to agree definitions for EVD-associated meningitis/ventriculitis, and a surveillance system was piloted in four centres in the UK and Ireland. Methods: Definitions were agreed based on those published previously and on clinical and microbiological criteria. An agreed dataset was developed to monitor patients after the insertion of an EVD and until the EVD was removed and the microbial aetiology was recorded. Findings: Four neurosurgical centres participated, with 61–564 patients surveyed in each unit. The vast majority of drains were cranial. Intracranial haemorrhage was the most common indication for the EVD insertion. Between 6% and 35% of EVDs were inserted by consultants rather than junior doctors. The proportion of patients who developed meningitis/ventriculitis varied from 3% to 18% and from 4.8 to 12.7/1000 EVD-days. Coagulase-negative staphylococci were the most common microbial causes. Conclusions: Routine and ongoing monitoring of patients with an EVD in situ to detect meningitis/ventriculitis presents logistical difficulties, and few units do so. This pilot study suggests that a national system of surveillance with agreed definitions and a methodology to enable unit-to-unit comparisons of EVD meningitis/ventriculitis is both necessary and feasible. This will, in turn, inform quality improvement processes leading to the minimization of infection.